Lifetime Exposure to Conversion Therapy and Psychosocial Health Among Midlife and Older Adult Men Who Have Sex With Men. (17th June 2020) - Meanley, Steven; Haberlen, Sabina A; Okafor, Chukwuemeka N; Brown, Andre; Brennan-Ing, Mark; Ware, Deanna; Egan, James E; Teplin, Linda A; Bolan, Robert K; Friedman, Mackey R; Plankey, Michael W
Abstract: Background and Objectives: Conversion therapies to minimize same-sex attractions are classified as a dangerous practice by numerous scientific institutions in the United States. These practices may contribute to poor long-term psychosocial health, thereby interrupting processes of healthy aging. Few studies have examined psychosocial differences between persons with and without prior experiences of conversion therapy. We assessed associations between prior conversion therapy experiences and psychosocial health among midlife and older men who have sex with men (MSM; age 40+ years). Research Design and Methods: Participants included a multicity sample of MSM ( N = 1, 156) enrolled in the Multicenter AIDS Cohort Study who completed health surveys (2016–2019) as part of their biannual study visits. Using multivariable regressions, we investigated the associations of prior conversion therapy with current depressive symptoms, internalized homophobia, post-traumatic stress, and cumulative psychosocial conditions. Using a trait-level measure (e.g., life purpose and perseverance), we tested whether resilience moderated these associations. Results: The full sample was predominantly non-Hispanic white with a mean age of 62.6 years. Fifteen percent of men ( n = 171/1, 156) reported prior conversion therapy. In multivariable models, men exposed to conversion therapy were more likely to have depressive symptoms and above-average internalized homophobia. Men exposed to conversion therapy had 2–2.5 times the odds of reporting 1 and ≥2 psychosocial conditions, respectively, compared with those who reported 0 conditions. Resilience did not moderate these associations. Discussion and Implications: Conversion therapies are nonaffirming social stressors for MSM and may compromise critical psychosocial aspects of healthy aging among MSM.